Passo a Paço nas redes: uma análise da comunicação do festival #SouManaus no Instagram - Gonçalves, Maria Clara Pereira (Brasil, 2024)
Considering the importance of cultural festivals for communities, the #SouManaus Passo a Paço stands out as an event that goes beyond artistic celebration, being essential for the economic, social, and cultural development of the Northern region of Brazil, especially Manaus. In this context, this research analyzes the communication between the festival organization and the public, focusing on Instagram, seeking to understand the adopted strategies and their impacts on public participation in the event. The theoretical framework of the study includes cultural marketing, digital communication, and cultural production in public relations. The methodology employed was analysis based on Framing Theory, focusing on the festival's Instagram posts and interactions in the years 2018, 2019, and 2022. To ensure accuracy, four types of frames were developed, based on similarities and patterns identified during data collection, involving the selection of relevant posts and interactions. A qualitative approach with documentary research was used. The aim is also to provide insights and recommendations to enhance future communication strategies of the festival and similar cultural events, through the development of a communication guide. This research not only seeks to understand the evolution of the festival's communication but also aims to provide a tangible contribution to its management and promotion, highlighting the importance of communication as a key element for the success and relevance of cultural events like the #SouManaus Passo a Paço.